1978
DOI: 10.1111/j.1398-9995.1978.tb01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Histamine Release by RNA, DNA and Aggregated IgG Examined in Rheumatoid Arthritis and Systemic Lupus Erythematosus

Abstract: Basophils from patients with rheumatoid arthritis (RA) respond to RNA, DNA and immune complexes (aggregated IgG) with histamine release. The RNA response was well correlated to the clinical activity of the disease, since histamine liberation was found in all patients with severe activity, whereas no liberation was observed in patients with moderate or quiescent activity. A less significant correlation was obtained with DNA and aggregated IgG. In contrast, no response was obtained with RNA, DNA and aggregated I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…IgE-type granulocyte-specific antinuclear autoantibodies were reported in sera of patients suffering from RA or Felty's syndrome.6 IgE-type anti RNA antibodies were also thought to be present in studies in which RNA could induce histamine release from basophils of RA patients. 22 IgM-type anti-IgE antibodies were detected in sera of healthy persons and in various patients.23 Our preliminary observations suggest that IgG class of anti-IgE antibodies may also be present in sera of some RA patients. While IgM-type antibodies agglutinated well, they did not release histamine.…”
Section: Discussionmentioning
confidence: 75%
“…IgE-type granulocyte-specific antinuclear autoantibodies were reported in sera of patients suffering from RA or Felty's syndrome.6 IgE-type anti RNA antibodies were also thought to be present in studies in which RNA could induce histamine release from basophils of RA patients. 22 IgM-type anti-IgE antibodies were detected in sera of healthy persons and in various patients.23 Our preliminary observations suggest that IgG class of anti-IgE antibodies may also be present in sera of some RA patients. While IgM-type antibodies agglutinated well, they did not release histamine.…”
Section: Discussionmentioning
confidence: 75%
“…Suggestions have previously patients with intrinsic asthma, the prevalence of been made that asthma and other allergic dis-IgM and IgG ON-ANA was higher than, but not orders might imply some involvement of autostatistically different from, those of controls, immunity (15) and of complex mediated type ANA occurred mostly in hospitalized patients III hypersensitivity (7). In the present material, those pahad IgA ANA and none had IgE ANA or tients having not received immunotherapy also C3-fixing ANA.…”
Section: Assay For Antinuclear Antibodiesmentioning
confidence: 99%
“…The prevalence of rheumatoid factor Agents which release histamine from heart-(IgM anti-IgG) in bronchial asthma and other lung preparations of normal guinea pigs have allergic diseases has varied between 0.8% (20) been found in serum and synovial fluid of and 17% (16) and of antinuclear antibodies rheumatoid patients (1) and basophils from (ANA) between 0.41% (20) and 16% (8). Im-patients with active rheumatoid arthritis may mune complexes have been demonstrated in respond to ANA and aggregated IgG with histhyposensitized patients (2,25) and it has been amine release, pointing to an involvement of suggested that histamine release from leuco-autoimmune type I reactions in the pathogenecytes of allergic donors may be caused by anti-sis (15). IgG antibodies (7).…”
mentioning
confidence: 99%
“…Basophils were stained and counted and the content of histamine per basophil was determined in the cell suspension as earlier described (10). The total number of leukocytes and eosinophils was counted by routine methods.…”
Section: Cell Count and Histamine Contentmentioning
confidence: 99%